Substance use and STI acquisition: Secondary analysis from the AWARE study. (1st December 2016) - Feaster, Daniel J.; Parish, Carrigan L.; Gooden, Lauren; Matheson, Tim; Castellon, Pedro C.; Duan, Rui; Pan, Yue; Haynes, Louise F.; Schackman, Bruce R.; Malotte, C. Kevin; Mandler, Raul N.; Colfax, Grant N.; et al.
Highlights: We studied relationships between drug use and prevalent and incident sexually transmitted infections (STIs). Substance use was related to STI rates and varied by gender and partner gender. Participation in substance use treatment was associated with increased STI rates. Focused interventions may be useful in STD clinics to reduce drug-related morbidity. Gender-specific sexual health interventions may be useful in substance use treatment. Abstract: Objectives: Sexually transmitted infections (STIs) are significant public health and financial burdens in the United States. This manuscript examines the relationship between substance use and prevalent and incident STIs in HIV-negative adult patients at STI clinics. Methods: A secondary analysis of Project AWARE was performed based on 5012 patients from 9 STI clinics. STIs were assessed by laboratory assay and substance use by self-report. Patterns of substance use were assessed using latent class analysis. The relationship of latent class to STI rates was investigated using Poisson regression by population groups at high risk for STIs defined by participant's and partner's gender. Results: Drug use patterns differed by risk group and substance use was related to STI rates with the relationships varying by risk behavior group. Substance use treatment participation was associated with increased STI rates. Conclusions: Substance use focused interventions may be useful in STI clinics to reduce morbidity associated with substance use. Conversely, gender-specific sexual health interventions may be useful in substance use treatment.